Supplementary Notes on the Magnetic Classification of Stony Meteorites - Nagata, Takesi (1978)
P(論文) A magnetic classification of stony meteorites on the basis of their saturation magnetization (I_s) and their major magnetic transition temperature (Θ_c) in the cooling process is revised by making use of recently reported chemical and petrographic data. The average values of (I_s in emu/gm, Θ_c in ℃) of enstatite chondrites (E), bronzite chondrites (H), hypersthene chondrites (L), carbonaceous chondrites (C) and achondrites (aC) are given by (48.0,764), (30.9,653), (12.5,656), (9.7,562) and (0.3,788) respectively. As either or both I_s and Θ_c values of each groups are distinctly separated from one another, stony meteorites can be classified reasonably well on the I_s∿Θ_c diagram. departmental bulletin paper